2015
DOI: 10.1136/bmjopen-2014-006001
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia prevalence and associated factors among lactating mothers in Ethiopia: evidence from the 2005 and 2011 demographic and health surveys

Abstract: ObjectiveTo identify factors associated with anaemia in lactating mothers in Ethiopia.DesignA cross-sectional secondary analysis of data pooled from two rounds of the 2005 and 2011 Ethiopian Demographic and Health Survey (EDHS) was used. A multivariate logistic regression model was applied to determine the factors associated with anaemia.PopulationA total of 7332 lactating mothers (2285 from EDHS 2005 and 5047 from EDHS 2011) were included from 11 administrative states of Ethiopia.Main outcome measuresLactatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
73
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(106 citation statements)
references
References 16 publications
15
73
6
1
Order By: Relevance
“…The overall prevalence was 60.3%, which is similar with the reported rate (61.1%) among women of reproductive age (15-45 years old), and with 20.3% of women having severe anemia [12]. Study in Somali found that anemia among lactating mothers was 43.8% and in the Afar region was 48.7% [13]. Study in India, the prevalence of lactation anemia was 81.7% in lactation up to 3 months [14].…”
Section: Associated Between Anemia In Breastfeeding Mothers With Asupporting
confidence: 76%
See 1 more Smart Citation
“…The overall prevalence was 60.3%, which is similar with the reported rate (61.1%) among women of reproductive age (15-45 years old), and with 20.3% of women having severe anemia [12]. Study in Somali found that anemia among lactating mothers was 43.8% and in the Afar region was 48.7% [13]. Study in India, the prevalence of lactation anemia was 81.7% in lactation up to 3 months [14].…”
Section: Associated Between Anemia In Breastfeeding Mothers With Asupporting
confidence: 76%
“…Predictions from several factors associated with anemia prevalence of breastfeeding mothers from the results of several studies are mother and husband's education, nutrition status or maternal body mass index (BMI), currently working, wealth index, ever use of family planning, availability of antenatal services and iron tablets, maternal BMI, duration of breastfeeding, and maternal smoking [13]- [15]. Meanwhile, the study found that anemia breastfeeding mothers were more common in the age group 20-30 years (78,8%), and with higher education (65,4%), as well as with low family income (65,4% <Rp.1,700,000,-).…”
Section: Associated Between Anemia In Breastfeeding Mothers With Amentioning
confidence: 99%
“…The zone has a total population of 2.5 million from which 94% are rural inhabitants. Subsistence farming is the dominant form of livelihood in the zone where only 15% of the population is in non-farm related jobs [23]. Dedo and Seka-Chokorsa Woredas are among the 18 administrative districts in Jimma Zone where the eight HFP-CCC project Kebeles are located.…”
Section: Methodsmentioning
confidence: 99%
“…It can be a result of pregnancy anemia that can be aggravated by blood loss during childbirth [8]. In addition, in the postpartum period, iron deficiency anemia can occur in breastfeeding mothers who are sensitive to iron depletion if energy and nutrient intake in their diet is inadequate [9]. In Burkina Faso, Sahelian country with limited resources [10], the maternal mortality ratio is still high and anemia is one of the major contributing factors [11].…”
Section: Introductionmentioning
confidence: 99%